Animal Biotechnology and Ethical Issues - Mahatthanadull*, Sanu; Thanaboripat, Dusanee (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2020)
Animal biotechnology is one of the main areas of biotechnology which concerns the application of animals, including transgenic animals, in various fields. Even though these transgenic animals can be useful for improving the welfare of humans and animals, the well-being of animals being used in the studies may be negatively affected. Ethical issues relating to experimentation on animals and the production of transgenic animals are discussed in this review, and included here is a consideration of the phenomena of ‘conditional ethical blindness’. Finding alternative protocols including the 4 Rs (reduction, refinement, replacement, and responsibility) to minimize the employment of animals in scientific procedures is one way to solve these problematic issues. These strategies can be successively utilized for certain animal biotechnological protocols and can be used to intelligently avoid unethical manipulation of animals. Keywords: animal; animal biotechnology; transgenic animal; ethical issue; ethics *Corresponding author: Tel.: +66814079000 E-mail: petchsanu@gmail.com